Effect of harvesting stages on seed quality of soybean (Glycine max L.) during storage - VR SHELAR; AP KARJULE; KC GAGARE (Seed Research, 2026)
An experiment was conducted to study the effect of different harvesting stages of soybean, on storability and seed quality during storage, with variety JS 335 grown in 3 consecutive kharif seasons. The crop was harvested at 85, 90, 95 and 100 days after sowing (DAS) and stored under ambient conditions. Bimonthly observations were recorded for germination, moisture content, vigour index and electrical conductivity from the seeds harvested at different stages. The maturity symptoms at physiological maturity (85 DAS) were yellowing of leaves, stem, pods with basal 2-3 dried as well as few upper green leaves. The IMSCS for germination was maintained for 12, 10, 8 and 6 months when the crop was harvested at 85, 90, 95 and 100 DAS, respectively. Similar trend was observed for vigour indices. The highest germination was observed in the seeds when the crop was harvested at physiological maturity and remained highest at subsequent storage period up to 12 months. Hence it is concluded that for maintaining the germination as well as other quality parameters, soybean should be harvested at physiological maturity which retain its viability during storage above IMSCS up to 12 months.